Reconfigurable sum–difference pattern by means of parasitic elements for forward‐looking monopulse radar. Issue 7 (1st August 2013) - Rocca, Paolo; Donelli, Massimo; Oliveri, Giacomo; Viani, Federico; Massa, Andrea
Abstract : This study describes the design of forward‐looking monopulse arrays able to reconfigure the radiation pattern from the sum mode to the difference one by electronically switching a set of parasitic dipoles placed in front of a driven array of radiating dipoles. The antenna architecture is synthesised by optimising the geometric parameters of the passive elements, namely their positions and lengths. The generation of the difference beam is yielded by imposing a phase displacement of π to the excitations of half active array and activating the parasitic array by turning‐on the switches that partition their lengths. As for the sum pattern, the effect of the parasitic dipoles is made negligible by turning‐off the switches. A set of representative results is reported and discussed to show the effectiveness of the proposed approach.